Both OsRecQ1 and OsRDR1 are required for the production of small RNA in response to DNA-damage in rice. - Hui Chen (Public Library of Science (PLoS), 2013)
Small RNA-mediated gene silencing pathways play important roles in the regulation of development, genome stability and various stress responses in many eukaryotes. Recently, a new type of small interfering RNAs (qiRNAs) approximately 20-21 nucleotides long in Neurospora crassa have been shown to mediate gene silencing in the DNA damage response (DDR) pathway. However, the mechanism for RNA silencing in the DDR pathway is largely unknown in plants. Here, we report that a class of small RNAs (qiRNAs) derived from rDNA was markedly induced after treatment by DNA-damaging agents [ethyl methanesulphonate (EMS and UV-C)], and that aberrant RNAs (aRNAs) as precursors were also highly induced after the DNA damage treatment in rice. However, these RNAs were completely abolished in OsRecQ1 (RecQ DNA helicase homologue) and OsRDR1 (RNA-dependent RNA polymerase homologue) mutant lines where either gene was disrupted by the insertion of rice retrotransposon Tos17 after the same treatment. DNA damage resulted in a more significant increase in cell death and a more severe inhibition of root growth in both mutant lines than in the WT. Together, these results strongly suggest that both OsRecQ1 and OsRDR1 play a pivotal role in the aRNA and qiRNA biogenesis required for the DDR and repair pathway in rice, and it may be a novel mechanism of regulation to the DDR through the production of qiRNA in plants.